Whole blood vs saline for MAP restoration in anesthetized piglets after non-traumatic hemorrhagic shock: an experimental study - Fabien Coisy; Dino Tikvesa; Florian Ajavon; Augustin Gamel; Laura Grau-Mercier; Thomas Sanchez; Marylène Bacle; Jean-Yves Lefrant; Thibaut Markarian; Xavier Bobbia (Scientific Reports)
Abstract In the management of hemorrhagic shock (HS), the restoration of adequate mean arterial pressure (MAP) while minimizing complications is critical. Whole blood (WB) has demonstrated physiological advantages over crystalloids such as normal saline (NS), yet direct comparisons in non-traumatic HS remain scarce. This study sought to evaluate the volume and hemodynamic efficacy of WB compared to NS in achieving a MAP of 60 mmHg in a porcine model of non-traumatic HS. The WB requirement and the NS volume necessary to restore MAP were 12 [10–14] and 23 [20–24] mL·kg-1, respectively (p < 0.01). One hour after resuscitation, mean arterial pressure (MAP) in the WB group was 69 [66–73] mmHg, and MAP in the NS group was 57 [55–64] mmHg (p < 0.05). Immediately after resuscitation, a median change of 1.4 [0.8–2.0] mmol·L-1 and -0.4 [-1.0–0.3] mmol·L-1 was observed in the WB and NS groups for base excess, respectively (p < 0.05). One hour after resuscitation, lactate levels decreased in median by -3.5 [-4.5 to -2.3] and -1.3 [-2.0 to -0.9] mmol·L-1 in the WB and NS groups, respectively (p < 0.05). Cardiac output and Syndecan-1 levels did not differ significantly between the groups. In this model of non-traumatic HS, WB showed greater efficacy in restoring MAP with a reduced infusion volume (1:2 WB:NS), exhibiting enhanced markers of metabolic recovery. Despite the comparable endothelial response, as indicated by Syndecan-1 levels, WB yielded more protracted hemodynamic benefits. These findings support the potential use of WB in early HS resuscitation and highlight the need for further investigation in non-trauma HS.